Opinion 2454: Charinidae Gray, 1849 (Reptilia, Squamata, Serpentes): emended to Charinaidae to remove homonymy with Charinidae Quintero, 1986 (Arachnida, Amblypygi); Ungaliopheinae McDowell, 1987 (Reptilia, Squamata, Serpentes): emended to Ungaliophiinae McDowell, 1987 - ICZN (Bulletin of Zoological Nomenclature, 2020)
Under the plenary power, the International Commission on Zoological Nomenclature has emended the spelling of the family-group name Charinidae Gray, 1849 (Reptilia, Squamata, Serpentes) to remove homonymy with Charinidae Quintero, 1986 (Arachnida, Amblypygi). The stem of the generic name Charina Gray, 1849 has been emended to Charina- to give the family-group name Charinaidae for the former while the latter family-group name based on Charinus Simon in Raffray, Bolivar & Simon, 1892 remains unchanged. The Commission has also used its plenary power to emend the spelling of the family-group name Ungaliopheinae McDowell, 1987 to Ungaliophiinae McDowell, 1987.
Keywords: Nomenclature; taxonomy; Arachnida; Serpentes; Charinidae; Charinaidae; Ungaliopheinae; Ungaliophiinae; Charinus; Charina; Ungaliophius; whip-spiders; boid snakes